ILMU KALAM SEBAGAI SARANA PENDIDIKAN AKHLAK DAN ETIKA UNTUK MENCERDASKAN GENERASI MUDA DALAM ERA MODERN - Nafiuddin; Hidayat, Khoirul; Khoiriyah, Zuhro'ul (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2025)
The focus of this research is on the significance of Ilmu Kalam as a tool for moral and ethical education in guiding youth in the modern era. Facing increasing moral challenges, today's younger generation requires an educational approach to instill strong moral values. This study aims to examine the role of Ilmu Kalam in moral and ethical education and its influence on character development among youth. Using a qualitative approach, this research employs library research to gather and analyze relevant literature. The findings reveal that integrating Ilmu Kalam into the formal education curriculum can boost students' moral and ethical awareness, motivating them to actively engage in social activities. The study concludes that applying Ilmu Kalam in education significantly contributes to shaping ethical and responsible individuals. This research recommends educational institutions integrate Ilmu Kalam into their curriculum as a strategic measure to guide and enlighten the younger generation.